The Role of Indonesian Language Learning in Shaping the Character of Students - Cecep Wahyu Hoerudin (GoAcademica Research & Publishing, 2022)
The function of language, particularly Indonesian, in moulding the character of a student is critical, and this is true both orally and in writing. An Indonesian instructor must understand that learning the language is about developing language skills rather than mastering the grammar of the language. Because of this, this study emphasized the issue of improving the competence of Indonesian language teachers so that they can better serve their students. In order to uncover the subject of inquiry, this study employs a qualitative technique combined with descriptive methodologies. According to the findings of the study, learning the Indonesian language has a major impact on the development of students' personalities and character. It is possible to receive assistance by learning to read and write as well as speak and listen.